Rancang Alat Vaporizer Pada Proses Pembuatan N-Butanol Dari N-Butil Butirat Dengan Proses Hidrogenasi Kapasitas 5.000 Ton/Tahun - Farliyanti (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2021)
The pre-design of the n-butanol plant is designed with a capacity of 5,000 tons/year, using n-butyl butyrate as raw material obtained from Yeshun Industry, China and Hydrogen obtained from PT. Airliquide, Cilegon and catalyst in the form of Cu/ZnO/Al2O3 obtained from Haldor Topsoe Company, Denmark. The location of the factory was established in the industrial area of ​​Pasuruan, East Java. The company will be established as a limited liability company (PT), with 135 employees. The factory operates 330 days a year, with a production process of 24 hours/day. n-Butanol is an intermediate used as a raw material for downstream industries in the textile, polymer, plastic, paint, surface coating, and pharmaceutical industries. The raw material is butyl butyrate in a liquid state at a temperature of 35°C with a pressure of 1 atm and hydrogen as raw material at a temperature of 35°C with a pressure of 7 atm. Production of butyl butyrate raw material in the main vaporizer at a temperature of 180 with a pressure of 10 atm. Vaporizer functions to raise the temperature from 180 °C to 280 °C and change the liquid phase into gas, Tube material: Carbon Steel SA+285 Grade C, Tube pitch (in) : 1, Tube layout: Triangular, OD (in) : 0, 5, BWG : 12, ID (in) : 0.282, Number of tubes : 532, Length (ft) : 11, Shell material : Carbon Steel SA+285 Grade C, Baffle material : Carbon Steel SA+285 Grade C. From design analysis It can be concluded that the Vaporizer helps the production process of making n-butanol from n-butyl butyrate with a hydrogenation process with a capacity of 5,000 tons/year.